Research trend mathematics problem solving in primary school: A bibliometric analysis using VOSviewer - Zahrah, Riza Fatimah; Turmudi, Turmudi; Prabawanto, Sufyani; Febriani, Winarti Dwi (Journal of Honai Math, 2024)
In addition to the cognitive aspects of the problem-solving process, an emotional dimension undoubtedly emerges. This study aims to conduct a bibliometric analysis to map articles focusing on the emotional side of mathematical problem-solving in elementary schools, using Google Scholar as the source and VOSviewer software for analysis. Data collection was facilitated through the reference management application Publish or Perish. This software enabled a comprehensive literature review on mathematical problem-solving in elementary schools. The keywords employed in data collection included "mathematical problem solving" and "primary school." The selected publications spanned the years 2020 to 2023. The results identified 338 articles pertinent to mathematical problem-solving in primary schools published over the past four years. The analysis revealed a declining trend in global research publications on this topic from 2020 to 2023. The bibliometric analysis indicated that "mathematical problem-solving in elementary school" had 166 links. Research findings on positive emotions and psychological well-being in mathematical problem-solving have shown increased student engagement and motivation. In conclusion, the current body of research on the emotional aspects of mathematical problem solving, particularly concerning positive emotions and psychological well-being in elementary school students, remains limited. This area presents significant opportunities for further investigation in future studies.